Globalization, the volatility of intermediate goods prices and economic growth - Thomas M. Steger; Lucas Bretschger (ETH Zurich, CER-ETH - Center of Economic Research, 2005)
We set up a dynamic stochastic model of a stylized economy comprising a final output sector (with traditional and modern firms) and an intermediate goods sector. It is shown that market integration reduces the volatility of the rate of return of capital invested in modern firms. The induced portfolio decision of households then leads to reallocation of capital from traditional to modern firms. Despite the presence of a reverse precautionary saving channel, the growth rate unambiguously increases due to the reallocation of capital. Empirical estimates for OECD countries confirm the theoretical results
Keywords: F1; O4; 330; globalization; trade in intermediate goods; portfolio decisions; economic growth; Globalisierung; Vorleistungen; Außenhandelspreis; Volatilität; Wirtschaftswachstum; Stochastisches Wachstumsmodell; Schätzung; OECD-Staaten